Subjective Evaluations: Discretionary Bonuses and Feedback Credibility - William Fuchs (Institute for the Study of Labor (IZA), 2013)
We provide a new rationale for the use of discretionary bonuses. In a setting with unknown match qualities between a worker and a firm and subjective evaluations by the principal, bonuses are useful in order to make the feedback from the firm to the workers credible. This way workers in good matches are less inclined to accept outside offers.
Keywords: D82; D83; D86; M5; 330; discretionary bonuses; feedback; signalling